Addicted to smartphones: exploring the prevalence of smartphone usage patterns and addiction among undergraduates in South Punjab-Pakistan - Bajwa, Ruqia Safdar; Abdullah, Haslinda; Wan Jaafar, Wan Munira; Abu Samah, Asnarul Khadi (Pakistan Medical Association, 2022)
Objective: To document the prevalence of smartphone use patterns and smartphone addiction among undergraduate university students in South Punjab, Pakistan. Methodology: This cross-sectional survey was conducted on undergraduate university students of 18-22 years recruited through multistage cluster random sampling technique from 2 universities of South Punjab, Pakistan from June to August 2020. Demographic information form and self-administered questionnaires measured smartphone addiction and smartphone use patterns. Data were analyzed with SPSS version 23. Results: Out of 621 respondents, 84.2% reported always keeping their smartphones. Nearly one-third (28.4%) used smartphones up to 3 hours a day, 23.3% three to 4 hours, and 48.3% used them more than 4 hours daily. Overall, 53% of students had high use of different smartphone patterns (interpersonal needs, entertainment, transaction, and information-seeking), and 51.4% scored high on the smartphone addiction scale. Conclusion: The frequency of high smartphone use patterns and addiction is prevalent among undergraduate university students. Long hours of use and accessibility of smartphones are essential factors that should be considered while developing preventive measures and strategies.